Identifying traumatization in young children through structured play: validation of the Odense Child Trauma Screening (OCTS) in Lithuania - Paulina Zelviene; Odeta Gelezelyte; Agniete Kairyte; Ask Elklit; Sille Schandorph Løkkegaard; Evaldas Kazlauskas (European Journal of Psychotraumatology)
Background: There is a need for valid methods to evaluate young children’s (4–8 years) psychological difficulties related to traumatic experiences. The Odense Child Trauma Screening (OCTS), developed by Danish researchers, is a play-based story stem assessment tool developed to screen for indicators of traumatization in young children. Just a few studies of the OCTS have been published so far.Objective: The current study aimed to test the reliability and convergent validity of the OCTS in the Lithuanian community and risk subsamples of young children aged 4–8 years.Method: The total sample consisted of 209 participants (58.9% girls) from the community (47.4%) and risk (52.6%) subsamples, Mage = 6.29 (SD = 1.48). All children were screened with the OCTS, and caregivers completed self-report questionnaires: demographics, the Child and Adolescent Trauma Screen-Caregiver (CATS-C), and the Strengths and Difficulties Questionnaire (SDQ).Results: The data suggests that the OCTS has good inter-rater reliability. The OCTS, SDQ, and CATS-C scores were significantly higher in the risk subsample, with small to large effect sizes. Boys and younger children (3–4-year-olds) scored higher on the OCTS. Out of all the OCTS stories, the Burnt hand story had significant correlation coefficients with all the CATS-C PTSD symptoms.Conclusions: The study provides initial information about the reliability and the validity of the OCTS and calls for further exploration of this instrument. There were also variations in scores between the Lithuanian data and an earlier study of the Danish sample. Future studies on the OCTS would benefit from further cross-cultural, reliability and the validity examination.